Short-term prognosis of unstable angina in the era of high-sensitivity cardiac troponin: insights for early rule-out strategies. Issue 8 (December 2020) - Gallone, Guglielmo; Magnoni, Marco; Vergani, Vittoria; Ceriotti, Ferruccio; Angeloni, Giulia; Scarano, Paola; Maseri, Attilio; Cianflone, Domenico
Abstract : Background: It is unclear if strategies to rule-out myocardial infarction (MI) based on a single high-sensitivity troponin T (hsTnT) measurement at the emergency department (ED) presentation may also exclude unstable angina. Methods: We measured hsTnT ex-post on the admission frozen blood sample of 644 subjects with Braunwald IIIB CK-MB-negative unstable angina. This analysis included the 240 patients with hsTnT value ⩽99th percentile reference limit (UA). We evaluated the clinical outcome of UA patients and the applicability of two rule-out strategies based on the combination of a non-ischemic ECG with (1) a single hsTnT value below the Limit-of-Detection (LoD), (2) a TIMI risk score ⩽1. Results: UA patients with hsTnT ⩽99th percentile reference limit had a favorable 30-day outcome [0.8% MI, 0% cardiovascular death (CVD)], but the rate of CVD/MI at 180-day was 4.7%. Sensitivities for UA were 94.6% according to the 'TIMI ⩽1-strategy' and 75.4% according to 'hsTnT-below-LoD-strategy', accounting for 5.4 and 24.6% missed diagnoses, respectively. A prognostic risk stratification to guide appropriate outpatient assessment in potential discharged unrecognized UA patients was developed: a risk score based on the combination of age >60 years and C-reactive protein >4.5 mg/L effectively stratified the 180-day CVD/MI occurrence: 0, 2.5 and 12.7% for score 0, 1 and 2 (log-rank = 0.001, C-statistic = 0.776). Conclusion: Single measurement hsTnT strategies, successfully tested to rule-out MI, may allow safe ED discharge of patients with a suspected acute coronary syndrome: even if UA may not be excluded, its short-term prognosis is favorable. UA patients with a C-reactive protein >4.5 mg/L and older than 60 years have a substantial medium-term cardiovascular risk and may benefit from a timely outpatient diagnostic assessment. Abstract : Supplemental Digital Content is available in the text.